PERSEPSI MASYARAKAT TENTANG TRADISI PAMOGIH DALAM PERNIKAHAN: STUDY KASUS DI DESA GUNOSARI KECAMATAN TLOGOSARI KABUPATEN BONDOWOSO - Amrotus Soviah; Umi Hanik (ASA, 2024)
The goal of marriage is to form a happy household and family in the context of sakinah mawaddah and warahmah families, which has implications for the benefit of the people. Each region has different wedding parties with their own characteristics in organizing them. The tradition of the Gunosari village community adds another way of arranging wedding ceremonies, namely, pamoghi. Traditions basically have a similar outline to offerings, begibeh (household furniture) and so on. Apart from the uniqueness of the term, this study also covers the process and its legal consequences. This research uses qualitative descriptive statistics and fieldwork. The results of this research show that the Pamogih tradition is a person's obligation to give items in a form such as necklaces, rings, dresses, and other household items agreed upon by both of them for celebrations, and these gifts are considered to have added value to society. This tradition is usually carried out before marriage ceremonies. Usually, goods are transferred after weddings. The legal consequences of violating or not following the Pamogih tradition include unfavorable opinions, slander, and community rejection.